Early lactate measurements for predicting in‐hospital mortality in paediatric sepsis. (29th August 2020) - Jaiswal, Priyanka; Dewan, Pooja; Gomber, Sunil; Banerjee, Basu Dev; Kotru, Mrinalini; Malhotra, Rajeev Kumar; Tyagi, Vipin
Abstract : Aim: We compared the performance of plasma lactate with high‐sensitivity C‐reactive protein (hs‐CRP), and paediatric sepsis‐related organ failure assessment (pSOFA) score for predicting mortality in septic children. Methods: Serial plasma lactate and hs‐CRP levels and pSOFA score was assessed during early hospital stay in septic children. Results: Out of 149 participants, 45 died. Plasma lactate at 0 h and 6 h was significantly higher, and lactate clearance was significantly lower in non‐survivors. The optimal cut‐off of plasma lactate at 6h for identifying mortality was 2.5 mmol/L (sensitivity 85% and specificity 74%). pSOFA score had the best predictive ability for mortality (AUC 0.89) followed by hs‐CRP at 0 h (AUC 0.86), hs‐CRP at 48 h (AUC 0.83), plasma lactate levels at 6 h (AUC 0.83), and plasma lactate at 0 h (AUC 0.67). Conclusion: pSOFA score, hs‐CRP and hyperlactemia at 6 h can identify septic children at risk of dying.